2004
DOI: 10.31899/rh4.1149
|View full text |Cite
|
Sign up to set email alerts
|

Informing the medical community in Guatemala about emergency contraception

Abstract: The general purpose of this project was to increase the awareness of and access to emergency contraception (EC) among the medical community in Guatemala. Specific project objectives included: 1) training three physicians as trainers in all aspects of EC; 2) adapting and disseminating scientific literature and informational materials about the method and about EC programs in Latin America and worldwide; and 3) training at least 250 participants about the characteristics of emergency contraception, its mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Some surveyed Nigerian and Nepalese providers reporting having received ECP training [ 41 , 45 ] while one Senegalese study found that a considerable proportion of providers (38%) had not received any ECP training [ 49 ]. Four studies described training initiatives that had led to improvements in provider knowledge and dispensing practice and more positive attitudes towards ECP [ 28 , 47 , 55 , 56 ]. A study of ECP from Guatemala included training for police officers, social workers and health professionals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some surveyed Nigerian and Nepalese providers reporting having received ECP training [ 41 , 45 ] while one Senegalese study found that a considerable proportion of providers (38%) had not received any ECP training [ 49 ]. Four studies described training initiatives that had led to improvements in provider knowledge and dispensing practice and more positive attitudes towards ECP [ 28 , 47 , 55 , 56 ]. A study of ECP from Guatemala included training for police officers, social workers and health professionals.…”
Section: Resultsmentioning
confidence: 99%
“…A study of ECP from Guatemala included training for police officers, social workers and health professionals. The findings indicated that these professionals not only shared their ECP knowledge and practice experiences with colleagues in their own organizations but across these sectors [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cascade capacity-building strategies can also be used to sensitize and involve stakeholders in non-health settings. In Guatemala, for example, five participants at a the pre-conference workshop in Quito in 2002 trained 10 trainers and organized 21 workshops, ultimately reaching 556 participants including service providers like nurses and physicians, NGO staff, and members of the justice system (Kestler and Ramirez 2004). In Ethiopia, a one day workshop model has been developed to train physicians, mid-level paramedical staff and community health workers (ECAfrique 2004;ESOG, ECAfrique, and MoH 2005).…”
Section: Capacity Building Among Ec Providersmentioning
confidence: 99%